Neurocryptococcosis and leptomeningeal carcinomatosis in metastatic prostate adenocarcinoma: differential diagnoses or overlapping symptoms? - Kutax Buiar, Ana Cláudia; de Almeida Vieira, Fernanda; Pasquini Neto , Ricardo; Gomes-Morila, Mariana Cristina; Sulzbach-Solanho, Gabriela; Sasso Pasquini , Daniela; Pruner-Vieira, João Victor; Figueroa-Magalhães, Maria Cristina (Brazilian Journal of Case Reports, 2022)
Acute headaches with red flags in patients with cancer may indicate metastasis or infection. This report describes a case of acute headache with red flags in a patient with metastatic prostate adenocarcinoma who presented a positive latex fixation test without pleocytosis in cerebrospinal fluid (CSF) analysis. Antifungal treatment was initiated based on the test’s high accuracy combined with the patient’s clinical condition and radiological impression of infectious meningitis, although we could not exclude associated secondary neoplastic involvement. Clinical improvement was first observed on D4 of treatment. On D14, CSF examination revealed therapeutic efficacy but positive oncotic cytology. The patient subsequently had new episodes of headache with warning signs and magnetic resonance imaging showed leptomeningeal carcinomatosis. Although neurocryptococcosis and leptomeningeal carcinomatosis are rare neurological complications, they may coexist with overlapping symptoms.